Political Participation and Pleasure in Green Lifestyle Journalism. Issue 1 (2nd January 2016) - Craig, Geoffrey
Abstract : This article examines the reportage of green lifestyle practices across the online sites of major British newspapers. The articulation of "green lifestyle journalism" in the study is suggestive of its complex identity, given its implication in existing orders of consumption while also expressive of emerging everyday practices that potentially and variously challenge those orders of consumption. The study enquires into whether such green lifestyle journalism stories are, in fact, reported across different online sites, and if so, in which publications and how such stories are classified within online menus. It also examines the range of reported environmental lifestyle practices and how they are attributed with meaning, including their engagement with the concept of pleasure and its association with political participation. The study reveals that the pleasures associated with sustainable living are often marginalized, and instead an ethical consumer is commonly posited who is variously cognitively deficient, worried about the environmental consequences of their everyday behavior, or concerned about their inability to realize their desires to engage in sustainable lifestyle practices. The article also examines those instances when the pleasures of a more sustainable lifestyle are represented as deriving from the implementation of environmental practices and technologies in everyday, domestic contexts, and also when they are illustrated as the product of civic and political engagements with issues of sustainability.